Juridical Analysis of Nurse Authority in Granting of Red Label Drugs in The Mandiri Nursing Practice - Aris Prio Agus Santoso; Tatina Siska Wardani (Universitas Katolik Soegijapranata Semarang, 2020)
Article 30 paragraph (1) of Law No. 38/2014 letter j explains that nurses are authorized to administer drug administration to clients, but the facts on the field nurses are actually arrested by Police for providing pharmaceutical preparations for clients. This shows that there has been an imbalance between regulations and facts on the ground.The problem in this study is how the nurse's authority in the service of giving red label medicines in the practice of independent nursing and how the legal protection of nurses in the practice of independent nursingThis research method uses a normative juridical approach, with secondary data collection, to prove whether it is true that nurses are prohibited from giving red label drugs. The data obtained were analyzed qualitatively.Based on the results of the study found that nurses have the authority to administer all drugs including red labeled drugs except drugs that contain narcotics and psychotronics. Nurses can provide these drugs both in terms of limitations and not. In that case, nurses obtain preventive legal protection by carrying out their obligations as nurses and fulfilling the rights of patients and not committing unlawful acts.